Effects of water hyacinth compost and biological agents (Trichoderma sp) on the growth and yield of shallots (Allium ascalonicum L.) in dry land - Lehar, Laurensius; Proklamita, Tri Luchi; Arifin, Zainal (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
Shallot (Allium ascalonicum L.) is one of leading vegetable commodities intensively cultivated by farmers for a long time, including farmers in East Nusa Tenggara (ENT). The purpose of this study was to produce water hyacinth compost with ability to interact with Trichoderma sp. in order to improve the shallot bulb quality cultivated in dry land. This factorial experimental research was arranged in a Split Plot Design with 10 treatments and 3 replications. There were 10 treatment combinations with 30 experimental plots. Two factors were tested in this research. The first factor was the water hyacinth compost as the main plot, namely: 15 ton ha⁻¹ water hyacinth compost (K1) and without water hyacinth compost (K2), while the second factor as a sub-plot was the concentration of Trichoderma sp., consisting of watering with plain water (as control) of 100 mL(P0), watering with a concentration of Trichoderma sp. 5 mL.L⁻¹ (P1), watering with a concentration of Trichoderma sp. 10 mL.L⁻¹ (P2), watering with Trichoderma sp. concentration 15 mL.L⁻¹ (P3) and watering with Trichoderma sp. 20 mL.L⁻¹ (P4). The treatment of water hyacinth compost fertilizer at 15 tons ha⁻¹ with a concentration of Trichoderma sp 20 mL.L⁻¹ resulted in the highest number of shallot leaves (84.27 strands) and tillers (10.82). The shallot bulb weight per plot was 2455.33 g, and the number of bulbs per plot was 350.40 bulbs.